A broad-spectrum pneumococcal vaccine induces mucosal immunity and protects against lethal Streptococcus pneumoniae challenge - Fang-Feng Chiu; Ling-Ling Tu; Wangxue Chen; Hongyan Zhou; Bing-Sin Liu; Shih-Jen Liu; Chih-Hsiang Leng (Emerging Microbes and Infections, 2023)
Pneumococcal disease is a major threat to public health globally, impacting individuals across all age groups, particularly infants and elderly individuals. The use of current vaccines has led to unintended consequences, including serotype replacement, leading to a need for a new approach to combat pneumococcal disease. A promising solution is the development of a broad-spectrum pneumococcal vaccine. In this study, we present the development of a broad-spectrum protein-based pneumococcal vaccine that contains three pneumococcal virulence factors: rlipo-PsaA (lipidated form), rPspAΔC (truncated form), and rPspCΔC (truncated form). Intranasal immunization with rlipo-PsaA, rPspAΔC, and rPspCΔC (LAAC) resulted in significantly higher IgG titres than those induced by administration of nonlipidated rPsaA, rPspAΔC, and rPspCΔC (AAC). Furthermore, LAAC immunization induced the production of higher IgA titres in vaginal washes, feces, and sera in mice, indicating that LAAC can induce systemic mucosal immunity. In addition, administration of LAAC also induced Th1/Th17-biased immune responses and promoted opsonic phagocytosis of Streptococcus pneumoniae strains of various serotypes, implying that the immunogenicity of LAAC immunization provides a protective effect against pneumococcal infection. Importantly, challenge data showed that the LAAC-immunized mice had a reduced bacterial load not only for several serotypes of the 13-valent conjugate pneumococcal vaccine (PCV13) but also for selected non-PCV13 serotypes. Consistently, LAAC immunization increased the survival rate of mice after bacterial challenge with both PCV13 and non-PCV13 serotypes. In conclusion, our protein-based pneumococcal vaccine provides protective effects against a broad spectrum of Streptococcus pneumoniae serotypes.